Atypical diabetes in children: ketosis-prone type 2 diabetes. (8th January 2013) - Vaibhav, Atul; Mathai, Mathew; Gorman, Shaun
Abstract : Ketosis-prone type 2 diabetes mellitus also known as atypical or flatbush diabetes is being increasingly recognised worldwide. These patients are typically obese, middle-aged men with a strong family history of type 2 diabetes. The aetiology and pathophysiological mechanism is still unclear but some initial research suggests that patients with ketosis-prone type 2 diabetes have a unique predisposition to glucose desensitisation. These patients have negative autoantibodies typically associated with type 1 diabetes but have shown to have human leucocyte antigen (HLA) positivity. At initial presentation, there is an impairment of both insulin secretion and action. β Cell function and insulin sensitivity can be markedly improved by initiating aggressive diabetes management to allow for discontinuation of insulin therapy within a few months of treatment. These patients can be maintained on oral hypoglycaemic agents and insulin therapy can be safely discontinued after few months depending on their β cell function.